2015
DOI: 10.1007/s00276-015-1448-1
|View full text |Cite
|
Sign up to set email alerts
|

Motor branches of the ulnar nerve to the forearm: an anatomical study and guidelines for selective neurectomy

Abstract: The number of motor branches of the ulnar nerve to the FCU varies from 2 to 4. An ideal approach for selective neurectomy of the FCU should start 4 cm above the medial epicondyle, and extend distally to 50% of the length of the forearm or just to the point where the ulnar artery joins the nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
13
0
2
Order By: Relevance
“…Similar results were obtained in our study. Paulos et al reported that the ulnar nerve distal to the elbow has two to five muscular branches to the flexor carpi ulnaris and one to two muscular branches to the flexor digitorum profundus [21]. The ulnar nerve may be strongly anchored to the forearm flexors by multiple branches.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in our study. Paulos et al reported that the ulnar nerve distal to the elbow has two to five muscular branches to the flexor carpi ulnaris and one to two muscular branches to the flexor digitorum profundus [21]. The ulnar nerve may be strongly anchored to the forearm flexors by multiple branches.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve bundles are consisted of multiple nerve fibers innervating different muscles. Previous studies showed that distribution of nerve fibers in some nerve bundles may be topographically arranged according to the targets before nerve branches 5153 . Detailed microanatomical studies revealed the fascicular topography of the brachial plexus 16,54 , indicating some level of somatotopic organization in C7.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,23 Stoffel's publication highlighted the importance of detailed knowledge of the anatomy and the variations of nerve supply. 13 Further cadaveric detailed anatomic studies of the terminal branches of the musculocutaneous 24 the median nerve 25 and the ulnar nerve 26 in cadavers has helped considerably in optimising surgical techniques and incisions when selective neurectomy is used to treat hypertonia in a functional Upper Limb. Selective Peripheral Neurectomy has been used for the treatment of neurectomy in various levels of the Upper Limb with a variety of results.…”
Section: Mini Reviewmentioning
confidence: 99%